Analysis of wear of cemented carbide cutting tools during milling operation of gray iron and compacted graphite iron - Da Silva M.B. (2011)
Cast iron is used to manufacture engine blocks and heads due to its mechanical and physical properties. The thermal conductivity and vibration absorption are some fundamental properties for these applications. Compacted graphite iron (CGI) has higher mechanical strength than gray cast iron and can be a great advantage in these types of mechanical parts. Although mechanical and physical properties are similar for both materials, CGI is considered to have poor machinability compared to gray cast iron, even when compared to alloyed gray cast iron. So it is important to investigate the behavior of the CGI for the most important cutting processes. While CGI Grade 450 is used for cylinder blocks, CGI Grade 350 is proposed for cylinder heads, because of higher thermal conductivity and better machinability. In the present work, two grades of gray iron, used to produce diesel engine cylinder heads, were compared to CGI Grade 350. Machining involves extensive plastic deformation ahead of the tool in a narrow chip zone and friction between the rake face and the chip, and these factors can interact extensively with the tool materials and start the wear mechanism. The investigations of cutting tool wear mechanism became necessary to fit the parameters and reduce the problems of stopping the machine for tool change. This work contributes to a better understanding of wear mechanisms of cutting tools used in milling operation of alloyed gray cast iron and compacted graphite iron using high cutting speeds. The main objective of this work is to verify the influence of the workpiece material and the cutting conditions on tool life and tool wear mechanism. The cutting process used is the dry face milling. Cemented carbide tools of class ISO K coated with Al2O3, using the technique of chemical vapor deposition at medium temperature (MTCVD), were used. The main conclusions are that workpiece material strongly influences tool life and tool wear involves different mechanisms. The wear mechanisms observed on the rake face at these conditions were abrasion and adhesion, at the end of tool life. Adhesion was the main wear mechanism at higher cutting speeds. © 2011 Elsevier B.V.